Prelinguistic communication development in children with childhood apraxia of speech: A retrospective analysis - Highman, Chantelle; Leitao, Suze; Hennessey, Neville; Piek, Jan (Informa Healthcare, 2012)
In a retrospective study of prelinguistic communication development, clinically referred preschool children (n = 9) aged 3–4 years, who as infants had failed a community-based screening program, were evaluated for features of childhood apraxia of speech (CAS). Four children showed no features and either delayed or normal language, five had from three-to-seven CAS features and all exhibited delayed language. These children were matched by age with 21 children with typically-developing (TD) speech and language skills. Case-control comparisons of retrospective data from 9 months of age for two participants with more severe features of CAS at preschool age showed a dissociated pattern with low expressive quotients on the Receptive-Expressive Emergent Language Assessment-Second Edition (REEL–2) and records of infrequent babbling, but normal receptive quotients. However, other profiles were observed. Two children with milder CAS features showed poor receptive and expressive development similar to other clinically referred children with no CAS features, and one child with severe CAS features showed poor receptive but normal expressive developmental milestones at 9 months and records of frequent babbling. Results suggest some but not all children with features of suspected CAS have a selective deficit originating within speech motor development.